Avaliação da suscetibilidade e do potencial a erosão laminar da bacia do ribeirão Sozinha (GO) - SOUZA, José Carlos de (2010)
The watershed has been designed as units of planning and environmental management. Areas are easily definable and have the systemic character, where the elements of the landscape, been natural or man-made, are interrelated continually, outbreak changes of energy and matter. In the function of this character the basins are presented as an ideal units for the application of methodologies that aim contribute to the planning of the land use. The purpose of this paper is present the results of the evaluation of potential laminar erosion in the basin of Ribeirão Sozinha, in the Estado de Goiás, through the integrated analyses of the physical means and the application of the prediction model. The methodology was elaborate by Salomão (1999), is an approach with qualitative and aims specialize the fragilities of the soil to the slat erosion in the basin. The basin of the ribeirão Sozinha, has approximately 430 km2, in the lands of the municipality of Leopoldo de Bulhões, Anápolis, Goianápolis, Bonfinópolis, Goiânia, Senador Canedo, Caldazinha and Bela Vista de Goiás. The geology of the basin are composed for ortho and paraderivados granulites and the granitoids of the complex granulites Anápolis-Itauçu and metasedimentary rocks of the group Araxá Sul de Goiás. The geomorphology is characterized by regional surfaces of planning of units Goiano central plateau and plateau chastened of Goiânia. The basin is on the biome Cerrado, and the remain are found in the area there are the physiognomies of Mata Ciliar, Mata Seca, Cerradão, Cerrado sentido restrito e Campo Sujo. Were definite to the basin four class of soil erodibility, High, for the Inceptisols and Entisols; Medium for the Ultisols, Red Yellow Red and Red Oxisol with a medium texture sandy, Low, for the Oxisol of medium texture and clay Plinthosols Petric, and None, for Gelisols. The basin was spatialized in six class of the slope (0% 3%), (3,1% 8%), (8,1% 12%), (12,1% 20%), (20,1% 45) e ( > 45%). With the crossing of the class of erodibility with the slope, we found five class of susceptibility to erosion, that we present on the basin as a percent: Class I Extremely susceptibly (12,87%); Class II Much susceptibly (35,32%); Class III Moderately susceptibly (27,63%); Class IV a little susceptibly (23,92%) and Class V a little to none susceptibly (0,26%). The class to the susceptibility to the erosion was crossing with the class of land use (Agriculture, Pasture, Vegetation and Urban Areas) was obtain three class of the potential to the slat erosion on the Ribeirão Sozinha, high potential 29,84%, of the area of basin, incompatible uses, medium potential (55,74%), incompatible uses, with the possibility of interventions with conservation practice, low potential (14,04%) with compatible use. The area of this study composed the part east of the Goiânia, and is a dynamic area, with different uses, and accordingly this, need for implementation of tools that enable use planning and land use in order to reduce the land degradation by extensive slat erosion.